Green approach to phytomediated synthesis of silver nanoparticles utilizing Ixora flower extract and their antioxidant potential - Sudha S. Patil; Narasimha Raghavendra (Hybrid Advances)
This study aims to investigate the antioxidant characteristics of silver nanoparticles (AgNPs) synthesized using Ixora flower extract (IFE). The IFE-AgNPs were characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD), Ultraviolet (UV)–Visible and Fourier-transform Infrared (FT-IR) spectroscopy techniques. The UV–Visible spectrum result indicated the surface plasmonic resonance (SPR) band at 410 nm, which is a characteristic band of AgNPs. The FT-IR spectroscopy results demonstrate that, the formation of IFE-AgNPs is caused by phytochemicals found in the Ixora flower extract. Computational studies by Monte Carlo (MC) simulation and density functional theory (DFT) confirms the electron donation property of Ixora flower extract molecules to the silver cations (Ag+). SEM and XRD results show that, the prepared Ixora flower extract-silver nanoparticles (IFE-AgNPs) nanoparticles had a spherical shape and ranged in size from 30 to 70 nm. The antioxidant capacity of IFE-AgNPs was confirmed through both DPPH and hydrogen peroxide method. The antioxidant activity enhances with increment in the IFE-AgNPs concentration and highest antioxidant activity observed at 40 mg/ml. The robust antioxidant activity of IFE-AgNPs suggests that, the prepared AgNPs is a great candidate for various biological applications. The results of this study might pave the way for the development of novel antioxidant qualities.